2021
DOI: 10.1002/anie.202101870
|View full text |Cite
|
Sign up to set email alerts
|

Using the Mechanical Bond to Tune the Performance of a Thermally Activated Delayed Fluorescence Emitter**

Abstract: If you like brighter TADF then you should put a ring on it. We report rotaxanes containing a carbazole-containing TADF luminophore in which the mechanical bond improves key photophysical properties, including the photoluminescence quantum yield and the singlet-triplet energy gap (DEST). Computational simulations, supported by X-ray crystallography, suggest this is due to weak interactions between the axle and macrocycle, enforced by the mechanical bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 118 publications
1
18
0
1
Order By: Relevance
“…H f ,H G and H H )a re shifted to lower ppm. Single-crystal X-ray diffraction analysis of [2]rotaxane 1&2 [37] suggests that, in keeping with previous reports, [24c] the high ppm chemical shift of the encircled triazole protons is due to CH•••N hydrogen bonds to the bipyridine Na toms (Figure 1c). In addition, anetwork of weak C À H•••p,C À H•••N and C À H•••O contacts between the macrocycle and axle are observed in the solid state.V iewed in as pacefill representation, it is clear that the macrocycle impinges significantly on the Cz fragment but does not interact with the BP unit, suggesting that any changes in the photophysical properties of the interlocked structures relative to the non-interlocked axle are likely to arise from modulation of the properties of the donor unit.…”
Section: Synthesis Of Interlocked Tadf Emitterssupporting
confidence: 90%
“…H f ,H G and H H )a re shifted to lower ppm. Single-crystal X-ray diffraction analysis of [2]rotaxane 1&2 [37] suggests that, in keeping with previous reports, [24c] the high ppm chemical shift of the encircled triazole protons is due to CH•••N hydrogen bonds to the bipyridine Na toms (Figure 1c). In addition, anetwork of weak C À H•••p,C À H•••N and C À H•••O contacts between the macrocycle and axle are observed in the solid state.V iewed in as pacefill representation, it is clear that the macrocycle impinges significantly on the Cz fragment but does not interact with the BP unit, suggesting that any changes in the photophysical properties of the interlocked structures relative to the non-interlocked axle are likely to arise from modulation of the properties of the donor unit.…”
Section: Synthesis Of Interlocked Tadf Emitterssupporting
confidence: 90%
“…[ 47 ] Recently, Zysman‐Colman, Goldup, Penfold, et al reported the fine modulation of photophysical properties of a carbazole−benzophenone‐based TADF emitter 4, a compound similar to 3 but with triazole groups in place of pyridine, upon interaction with macrocycle 5 to give rotaxane systems 4⊂5 and 4⊂5 2 ( Figure a). [ 48 ] 1 H NMR and single‐crystal X‐ray diffraction analyses showed the triazole protons to be hydrogen bonded to the macrocycle bipyridine moiety (Figure 6b). Photophysical measurements in toluene probed the effect of mechanical bond formation on the optoelectronic properties.…”
Section: Supramolecular Tadf: a Diverse Lineupmentioning
confidence: 99%
“…Reproduced under the terms of the CC‐BY 4.0 license. [ 48 ] Copyright 2021, The Authors, published by Wiley‐VCH.…”
Section: Supramolecular Tadf: a Diverse Lineupmentioning
confidence: 99%
See 1 more Smart Citation
“…[41,[44][45][46] We envision that the bulky macrocycle around the fluorescent dye could enhance the rigidity of the fluorophore by inhibiting its local molecular motions. To date, methods with encapsulation structures, such as host-guest complexes [27][28][29][30][31][32][33] and rotaxane structures, [47][48][49][50][51] have been used to prevent the molecular motions of fluorophores. However, these strategies possess some inherent limitations, such as (i) unstable structure in different solvents, derived from the supramolecular structure based on non-covalent intermolecular structure, and (ii) applicability to a limited variety of fluorescent dyes because of the requirement of the strong affinity between the macrocycles and the target fluorophores.…”
Section: Introductionmentioning
confidence: 99%